A holistic model of handling conflicts : lessons from a multicultural urban congregation in Britain - Jun, Guichun (Regnum studies in mission., 2020)
"This book is a systematic and comprehensive investigation into conflicts in a multicultural congregation in an urban area in the UK. It provides a comprehensive account of conflict through analysing and interpreting diverse types of conflict from a combined range of perspectives of anthropology, sociology and theology. It also profoundly explains the dynamics of conflict phenomena from a multidimensional perspective to understand the nature, scale and intensity of multifactorial and multifaceted conflicts in the four conflict domains: interpersonal behavioural conflict, cultural conflict, theological conflict and political conflict. The most significant contribution of this book is to establish a holistic model of handling diverse types of conflict for peace-making, peace-keeping and peace-building through employing conflict resolution, settlement, management and transformation in a multicultural congregational setting."--Publisher.